Characterization and antimicrobial susceptibility of Escherichia coli, Salmonella enterica isolated from Uvurkhangai province in Mongolia (Mongolian Journal of Agricultural Sciences, 2023)
The incidence of infectious diseases caused by the Enterobacteriaceae family of Uvurkhangai province in Mongolia is not decreasing and is recurring despite the implementation of preventive measures in the province. Nowadays, when the resistance of microorganisms negatively affects the health of humans and animals, food safety, the environment, and the economy, the lack of effective antibiotics for treatment is the reason for the research work on this topic. Based on the outbreak and surveillance of infectious diseases for the past 5 years, the pathological materials were received in the veterinary laboratory, two strains of Escherichia coli and also two strains Salmonella enterica subsp. abortus equi were isolated, and identified by conventional bacteriological and molecular methods. The antimicrobial susceptibility of the pathogen was determined using the disc diffusion method. The strains of E. coli were resistant to several antimicrobials, including vancomycin and neomycin, intermediate to colistin. The Salmonella enterica subsp. abortus equi showed resistance to ampicillin, vancomycin, gentamicin, and neomycin. Due to the presence of antimicrobial resistance, the results suggest a risk to public health as these pathogens. However, the four isolated bacteria in the family of Enterobacteriaceae showed susceptibility to groups of tetracycline and streptomycin. As a result of this study, it was determined that treatment with tetracycline and streptomycin is effective against bacterial infections caused by the Enterobacteriaceae group.